2011
DOI: 10.1021/ct100508y
|View full text |Cite
|
Sign up to set email alerts
|

Exciton/Charge-Transfer Electronic Couplings in Organic Semiconductors

Abstract: Charge transfer (CT) states and excitons are important in energy conversion processes that occur in organic light emitting devices (OLEDS) and organic solar cells. An ab initio density functional theory (DFT) method for obtaining CT-exciton electronic couplings between CT states and excitons is presented. This method is applied to two organic heterodimers to obtain their CT-exciton coupling and adiabatic energy surfaces near their CT-exciton diabatic surface crossings. The results show the new method provides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 56 publications
1
65
0
Order By: Relevance
“…A more sophisticated yet still approximate alternative, which would require an extension of the current FDE-ET formalism, is to construct approximate excited-state wavefunctions on the basis of TDDFT results, as employed in Ref. 62.…”
Section: Spin States Of the Diabatic Wavefunctions And Coupling Tomentioning
confidence: 99%
“…A more sophisticated yet still approximate alternative, which would require an extension of the current FDE-ET formalism, is to construct approximate excited-state wavefunctions on the basis of TDDFT results, as employed in Ref. 62.…”
Section: Spin States Of the Diabatic Wavefunctions And Coupling Tomentioning
confidence: 99%
“…Approximate CT wave functions have previously been constructed using, e.g., constrained DFT to study their coupling to localized excitations derived from TDDFT. 27 GW -BSE allows to derive both from the same Hamiltonian, and to this end, intermolecular CT excitations of types A – B + and A + B – are constructed within GW -BSE-DIPRO as product states from the respective monomer single-particle orbitals. All the couplings between the CT excitations, as well as to the localized monomer excitons, are calculated.…”
Section: Introductionmentioning
confidence: 99%
“…For example, this method has been used to calculate charge transfer rates via Marcus theory. 29,3742 In 2000, Kim et al suggested that a charge could be treated via the Langevin equation. 43 Beyond CDFT and LMD, many other models of charge transport in organic semiconductors have been proposed (see ref.…”
Section: Introductionmentioning
confidence: 99%